Sosialisasi Dan Pendampingan Pembuatan Legalitas Usaha Melalui Online Single Submission Di UMK Mamah Dedeh Kitchen Dan Zulich Clean And Care - Hidayah, Sanita Nur; Airawaty, Diana (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Business legality is crucial for the development and sustainability of a business. One of the beneficial functions of legality, especially for Micro, Small, and Medium Enterprises (UMKM), is to facilitate business owners in obtaining funding to optimize their operations and compete in the global market. The government is making efforts to assist UMKM in obtaining business legality, including the issuance of the Business Identification Number (NIB) through the Online Single Submission (OSS) website. The government provides various forms of assistance, guidance, and training. The increasing number of UMKM each year indicates that new entrepreneurs may lack knowledge and require assistance in obtaining business legality. Activities are conducted to address this issue while introducing and enhancing understanding of the process of obtaining the Business Identification Number (NIB) through Online Single Submission (OSS). This outreach and assistance are carried out for UMK Mamah Dedeh Kitchen and UMK Zulich Clean and Care methods applied include socialization, training, and mentoring. The implementation of these activities involves the delivery of theory and practical aspects related to the business legality registration process. Providing NIB assistance to Mamah Dedeh Kitchen and Zulich Clean and Care business owners has had a positive impact. Initially, many entrepreneurs considered obtaining a business license to be a complex, time-consuming, and costly process. However, after receiving guidance, they now realize that the NIB application process through OSS is straightforward and offers numerous benefits. Â